BRIEF CHARACTERISTIC OF EUROPEAN GENOTYPE TICK-BORNE ENCEPHALITIS VIRUS STRAINS IDENTIFIED IN SIBERIAN REGION - S. E. Tkachev; I. V. Kozlova; Y. P. Dzhioev; M. M. Verkhozina; E. K. Doroschenko; O. V. Lisak; O. V. Suntsova; V. I. Zlobin; A. I. Paramonov; A. Y. Tikunov; A. V. Lyapunov; N. V. Tikunova; et al. (Acta Biomedica Scientifica, 2014)
The molecular-genetic analysis of 13 strains of Western genotype TBEV isolated in Western and Eastern Siberia demonstrated two groups of strains differed geneticallyfrom each other and had a high level of E gene sequences homology within each group. Nevertheless, the heterogeneity of biological propertiesfor some strains within a group was observed.